Post weld heat treatment effects on SMSS deposit mechanical properties - Zappa, Sebastián (2015)
Supermartensitic stainless steels have been developed as an alternative technology, mainly for oil and gas industries. In these steels, the post-weld heat treatments are usually double tempering treatments, to ensure the complete tempering of martensite and high austenite content. The aim of this work was to study the effect of post-weld heat treatments (solubilizing with simple and double tempering) on the mechanical properties of a supermartensitic stainless steel deposit obtained with a FCAW wire welded under gas shielding.